2013
DOI: 10.1111/jsap.12147
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical duration of canine ovariectomy and ovariohysterectomy in a veterinary teaching hospital

Abstract: Ovariectomy is not associated with shorter surgical times or smaller abdominal incisions than ovariohysterectomy when employed by inexperienced surgeons. As no major complications novel to ovariectomy occurred in this cohort of dogs, this study adds support to the existing literature indicating that ovariectomy is an acceptable alternative to ovariohysterectomy for canine neutering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Similarly, the length of skin incision varies between 4 -9 cm (Freeman et al, 2014) and 9.6 ± 3.4 cm (Harris et al, 2013). In the present study, it was observed that total surgery time (58.50 ± 6.28 minutes) and length of skin incision (10.75 ± 1.40 cm) in the experiment group was consistent with the above mentioned studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similarly, the length of skin incision varies between 4 -9 cm (Freeman et al, 2014) and 9.6 ± 3.4 cm (Harris et al, 2013). In the present study, it was observed that total surgery time (58.50 ± 6.28 minutes) and length of skin incision (10.75 ± 1.40 cm) in the experiment group was consistent with the above mentioned studies.…”
Section: Discussionsupporting
confidence: 91%
“…It is known that the total surgery time of OVH performed by experienced veterinary surgeons is 17 minutes on average with 1.5 -2.5 cm width skin incision (Michelsen et al, 2012;Korkmaz et al, 2019). In contrast when students perform OVH, the duration of surgery time varies between 60 and 135 minutes, associated with the level of the students (Zeugschmidt et al, 2016) and the nature and type of teaching procedures such as how surgery is supervised (Bowlt et al, 2011;Harris et al, 2013;Freeman et al, 2014;Gates et al, 2018) and whether training includes tools such as virtual reality (Hunt et al, 2020), video recordings and plastic spay simulator models (Read et al, 2016;Shaver et al, 2019;Annandale et al, 2020). Similarly, the length of skin incision varies between 4 -9 cm (Freeman et al, 2014) and 9.6 ± 3.4 cm (Harris et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the studies reviewed here only two major complications were reported, both by Harris et al (2013). Of these complications one, bladder laceration, would be expected to occur more commonly in OVH procedures due to the more caudal placement of the distal ligature.…”
Section: Harris Et Al (2013)mentioning
confidence: 88%
“…Laparoscopic neutering, in particular, is regularly used in a number of veterinary hospitals and is gaining greater acceptance and preference among veterinary practitioners. Most of the techniques currently used in small animal reproduction are for gonadectomies (ovariectomy in females, and cryptorchidectomy and vasectomy in males); however, ovariohysterectomy can readily be performed by laparoscopy if indicated (Dupré et al., ; Gower & Mayhew, ; Harris, Adams, Fordyce, & Ladlow, ; Milovancev & Townsend, ). New applications of endoscopic surgery, and where it has greatest potential to become the gold standard, in veterinary medicine will likely parallel the trends in human medicine (Khatuja et al., ).…”
Section: Endoscopic Surgery For Small Animal Reproductionmentioning
confidence: 99%